Dentigerous cyst associated with a supernumerary tooth in the maxillary incisal region - a case report - O.A. Erinoso; S.O. Fadeyibi; M.O. Gbotolorun; M.O. Adeyemi (Nigerian Dental Association, 2020)
Dentigerous cysts are defined as developmental odontogenic cysts, which surround the crown of an impacted tooth. It is caused by fluid  accumulation between the reduced enamel epithelium and the enamel surface, resulting in a cyst with the tooth crown located within the lumen. This paper reviews the pathogenesis, clinical features and the behaviour of dentigerous cyst. It also presents a case of a slow growing, painless swelling in the maxillary incisal region of 3 years duration. Detailed clinical, radiological and histopathological investigations aided the definitive diagnosis of dentigerous cyst. The cystic mass was enucleated with the impacted tooth in situ under local anesthesia. The operative site healed uneventfully and a removable partial  denture was fabricated to improve aesthetics, speech and masticatory function.